Colorimetric and fluorescence probe for the detection of nano-molar lysine in aqueous medium. Issue 45 (1st November 2016) - Adhikari, Susanta; Ghosh, Avijit; Mandal, Sandip; Guria, Subhajit; Banerjee, Prajna Paramita; Chatterjee, Ansuman; Das, Debasis
Abstract : A new BODIPY based lysine selective probe, THBPY, is synthesized and detects nano-molar lysine in aqueous medium, exhibiting both a visible change in color from yellow-green to orange and a change in the fluorescence profile. Abstract : A single crystal X-ray structurally characterized BODIPY based probe, THBPY, derived from 4-hydroxy-5-isopropyl-2 methyl-isophthalaldehyde, detects nano-molar lysine in aqueous medium. In the presence of lysine, THBPY visibly changes its color and fluorescence profile due to the formation of a stable imine bond. A distinctive color change allows for facile discrimination over other amino acids in a wide range of concentrations of lysine. The detection limit for lysine is 0.001 μM by a fluorescence method and 0.01 μM by a colorimetric method. The probe shows good reversibility for multiple uses and cleanly discriminates between lysine and other amino acids. Density functional theoretical studies closely resemble experimental results.